1997
DOI: 10.1002/hep.510260305
|View full text |Cite
|
Sign up to set email alerts
|

Serum autoantibodies in chronic hepatitis C: Comparison with autoimmune hepatitis and impact on the disease profile

Abstract: ANA-H and/or SMA-AA does not exclude AIH, the characterAntibodies to nuclei (ANA), smooth muscle (SMA), and ization of ANA and SMA may help to discriminate between liver/kidney microsomes type 1 (anti-LKM1) may occur in the two conditions. As compared with the seronegative counchronic hepatitis C. Distinct subspecificities, including ANA terpart, autoantibody-positive chronic hepatitis C is more with the homogeneous pattern (ANA-H) and SMA with anticommon in females and exhibits a more severe biochemical actin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

26
119
7
5

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(157 citation statements)
references
References 27 publications
26
119
7
5
Order By: Relevance
“…Consistent with results from previous studies, 10,28,31,32,33 we found that the prevalence of autoantibodies in HCV patients was significantly higher than those in uninfected controls. Our study showed a high prevalence of ASMA, ANA and RF.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Consistent with results from previous studies, 10,28,31,32,33 we found that the prevalence of autoantibodies in HCV patients was significantly higher than those in uninfected controls. Our study showed a high prevalence of ASMA, ANA and RF.…”
Section: Discussionsupporting
confidence: 82%
“…9 Other investigators have reported that the prevalence of ANA, ASMA and AL/KM was higher than in normal subjects. 10,31 In one study, the prevalence of ASMA was found to be 30%, 31 the same percentage found in our study. It is of interest that our results are in accord with the prevalence found in another study carried out in the Middle East.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…A variety of immunological abnormalities have been described in patients with chronic hepatitis C, and in particular, a high prevalence of positivity for autoantibodies was reported (14,15). Furthermore, patients with autoantibodies had more severe portal-periportal necroinflammation (15).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients with autoantibodies had more severe portal-periportal necroinflammation (15). Many patients diagnosed with autoimmune hepatitis before the availability of hepatitis C virus testing were thought to have hepatitis C virus infection (2).…”
Section: Discussionmentioning
confidence: 99%